1986
DOI: 10.1017/s0025315400043009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Western mackerel (Scomber scombrus) spawning stock composition during the spawning season

Abstract: INTRODUCTIONTwo groups of mackerel (Scomber scombrus L.) are recognised by the International Council for the Exploration of the Sea (I.C.E.S.) for stock assessment purposes in the north-east Atlantic. The North Sea ‘stock’, which overwinters along the edge of the Norwegian Trench and spawns off the south coast of Norway, in the Skagerrak, Kattegat and the central North Sea (Hamre, 1980), and the Western ‘stock’, which overwinters and spawns along the edge of the continental shelf from the west of Ireland to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…The catch composition at age also varies in the different areas of the northeast Atlantic (ICES, 1996(ICES, -2001. As previously stated, Dawson (1986) and Eltink (1987) linked differences in growth to gradual spatio-temporal changes in length at age during the migration of mackerel through European waters. Another cause of variability in mackerel growth rate may be the effect of population density, as found by Mackay (1973), Overholtz (1989) and Neja (1995) in the northwest Atlantic, especially in the youngest ages.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The catch composition at age also varies in the different areas of the northeast Atlantic (ICES, 1996(ICES, -2001. As previously stated, Dawson (1986) and Eltink (1987) linked differences in growth to gradual spatio-temporal changes in length at age during the migration of mackerel through European waters. Another cause of variability in mackerel growth rate may be the effect of population density, as found by Mackay (1973), Overholtz (1989) and Neja (1995) in the northwest Atlantic, especially in the youngest ages.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, Eltink and Gerritsen (1982), Dawson (1986) and Eltink (1987) rule out the hypothesis that there are two subpopulations in the western area and postulate an alternative explanation, stating that the growth differences are due to gradual spatial and temporal changes in the length at age during migration. The largest fish of a certain age reach spawning areas earlier and also leave for feeding areas earlier than smaller ones, which would lead to successive changes in length and weight at age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During spawning in the southern area, the length of fish reveals a gradual phenomenon in which the largest spawners appear in the catch in March and April, while a greater abundance of young spawners appears in May, when recruitment to the spawning stock is effectively taking place (Eltink et al, 2002). Dawson (1986) and Eltink (1987) also found that migration of western component mackerel to the spawning area occurs in an agelength sequence, from the oldest to the youngest. The exploitation pattern of the handline fishery was constant in the period studied except for 1992, when there was a small increase in exploitation of individuals of age 1, which were hardly exploited at all in other years.…”
Section: Discussionmentioning
confidence: 87%